Nutritional value and consumer acceptability of smoothies in the UK and KSA - Daffa, Basma (2020)
Increased vegetable consumption could decrease the risk of cardiovascular disease (CVD), obesity and certain cancers. Smoothies are one of the ways to increase vegetable consumption. The aim of this study was to develop a vegetable-containing smoothie with improved nutritional value and consumer acceptability. A survey was conducted on university students (from UK and KSA) to assess their opinions, followed by tasting sessions with several potential smoothies. Following this, the most acceptable smoothie recipe was selected for further analysis. Some key nutritional parameters; ascorbate, antioxidants, phenolics, sugars and fibre of the novel smoothie were measured and compared with commercial smoothies available in the UK market. Also, the retention and stability, during 1, 3 and 5 days of storage at 4°C of these nutrients were analysed. The survey revealed that there was good awareness of the 5 A DAY requirement in the UK, but only fair awareness in the KSA student sample of increasing fruit and vegetable (F&V) intake. Price was a potential barrier for students. Tasting trials indicated that the UK student’s acceptance was limited by firstly taste then texture and colour. The novel smoothie based on beetroot and red pepper appeared to be most acceptable. The nutritional value of this smoothie (ascorbate 30 mg/100mL, antioxidant capacity 1031µmoles Trolox Equivalents/100mL, phenolics 57mg Gallic Acid Equivalents/100mL and fibre 6g/100mL) appears to be higher than current commercial smoothies. It was also slightly lower in total sugars with 9g/100mL. This smoothie retained the nutritional benefits of the constituent F&Vs during processing. Also, the nutritional value of the designed smoothie was stable during storage at 4oC over 5 days, apart from ascorbate which declined dramatically. Potential commercial barriers included the high viscosity. Preliminary experiments were carried out to investigate the potential to reduce viscosity using enzyme cocktails. The smoothie containing 47% vegetables and 53% fruit could be one of the easiest ways of increasing F&V consumption, particularly amongst students, to maintain a healthy diet.